PELATIHAN PEMBUATAN ECO-ENZYME DARI LIMBAH RUMAH TANGGA PADA KELOMPOK TANI DESA BANGSRING KABUPATEN BANYUWANGI - Istanti, Ari; Susilowati, Erlin; Nurmala Sari, Eka (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2025)
Domestic waste is one of the largest contributors of waste to the environment. The side effects of improper waste processing are environmental contamination. Public awareness of the impact for domestic waste management must be emphasized. This program was conducted with the farmer association of Bangsring, Banyuwangi Regency. The purpose of this program is to encourage local community awareness of environmental sustainability and provide knowledge of the importance of utilizing and processing domestic waste into Eco-Enzyme. This program is implemented through several main stages that refer to the indicators of the success of the community service program, namely: (1) survey to obtain problems and determine problem solving; (2) socialization; (3) training of eco-enzyme production; (4) monitoring and evaluation. The training of eco-enzyme production in Bangsring was successfully implemented, and the community has responded well to it. This is evidenced by the enthusiasm of the participants during discussions and practices of producing eco-enzyme, all the way through to harvesting the eco-enzyme's output and implementing it.